The Role of the Gut Microbiome in Colorectal Cancer - Chen, Grace Y. (Clinics in Colon and Rectal Surgery, 2018)
There is increasing evidence that the gut microbiome, which consists of trillions of microbes representing over 1,000 species of bacteria with over 3 million genes, significantly impacts intestinal health and disease. The gut microbiota not only is capable of promoting intestinal homeostasis and antitumor responses but can also contribute to chronic dysregulated inflammation as well as have genotoxic effects that lead to carcinogenesis. Whether the gut microbiota maintains health or promotes colon cancer may ultimately depend on the composition of the gut microbiome and the balance within the microbial community of protective and detrimental bacterial populations. Disturbances in the normal balanced state of a healthful microbiome, known as dysbiosis, have been observed in patients with colorectal cancer (CRC); however, whether these alterations precede and cause CRC remains to be determined. Nonetheless, studies in mice strongly suggest that the gut microbiota can modulate susceptibility to CRC, and therefore may serve as both biomarkers and therapeutic targets.
Keywords: dysbiosis; inflammation; oncomicrobes